1992
DOI: 10.1366/000370292789619368
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Near-Infrared Fourier Transform Raman Spectroscopy in Food Analysis

Abstract: The 1064-nm excited Fourier transform (FT) Raman spectra have been measured in situ for various foods in order to investigate the potential of near-infrared (NIR) FT-Raman spectroscopy in food analysis. It is demonstrated here that NIR FT-Raman spectroscopy is a very powerful technique for (1) detecting selectively the trace components in foodstuffs, (2) estimating the degree of unsaturation of fatty acids included in foods, (3) investigating the structure of food components, and (4) monitoring changes in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
77
0
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(78 citation statements)
references
References 7 publications
0
77
0
1
Order By: Relevance
“…Feathers were probed with a 780 nm 150 mW diode laser, through a 50Â Mplan apochromatic objective lens (Olympus, Melville, NY, USA) and 100 mm pinhole aperture (BX51 confocal microscope, Olympus, Melville, NY, USA). Carotenoids have a very broad pre-resonance range, 16,17 and hence the spectra collected with the 780 nm excitation wavelength were analytically useful, and were comparable to spectra collected with 532 nm excitation (532 nm spectra not shown). The green wavelength may be more sensitive to uorescent impurities (i.e.…”
Section: Data Collectionmentioning
confidence: 80%
“…Feathers were probed with a 780 nm 150 mW diode laser, through a 50Â Mplan apochromatic objective lens (Olympus, Melville, NY, USA) and 100 mm pinhole aperture (BX51 confocal microscope, Olympus, Melville, NY, USA). Carotenoids have a very broad pre-resonance range, 16,17 and hence the spectra collected with the 780 nm excitation wavelength were analytically useful, and were comparable to spectra collected with 532 nm excitation (532 nm spectra not shown). The green wavelength may be more sensitive to uorescent impurities (i.e.…”
Section: Data Collectionmentioning
confidence: 80%
“…12 Our experiment revealed that this relationship also occurs for carotenoids (i.e., crocetin, ␤-carotene, and lycopene) measured in situ by FT-Raman spectroscopy. The observed 1 shift toward red is correlated with an increasing number of conjugated double bonds in the carotenoid chain, i.e., 1536 cm Ϫ1 (7) 3 1524 cm Ϫ1 (9) 3 1510 cm Ϫ1 (11). Contrary to that, no correlation is observed for v 2 and v 3 modes (see Table I).…”
mentioning
confidence: 81%
“…12,13 NIR-FT-Raman spectroscopy also gives a strong enhancement of carotenoids due to the known preresonance effect; furthermore, the disturbing fluorescence effect of biological material usually observed when laser excitation is performed in the visible wavelength range, is avoided. 11 Strong bands of carotenoids are observed in the Raman spectrum within the 1500 -1550 and 1150 -1170 cm Ϫ1 ranges due to in-phase CϭC ( 1 ) and C-C stretching ( 2 ) vibrations of the polyene chain. Additionally, in-plane rocking modes of CH 3 groups attached to the polyene chain and coupled with C-C bonds are seen as a peak of medium intensity in the 1000 -1020 cm Ϫ1 region.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…These sensitivities are due to the Raman resonance phenomenon and not to the classical Raman phenomenon that occurs in Raman experiments. Resonance Raman spectroscopy has been applied to analyse selectively trace components such as pigments (Merlin et al, 1994;Ozaki et al, 1992), cholesterol (LeCacheux et al 1996) and vitamin A. Another way to obtain an enhanced Raman signal is to use surface-enhanced Raman spectroscopy (SERS) (Dou et al 1999).…”
mentioning
confidence: 99%